Evolution of courtship display in Estrildid finches: dance in relation to female song and plumage ornamentation - Soma, Masayo; Garamszegi, László Z. (Frontiers in Ecology and Evolution, 2015)
Estrildid finches are known for great interspecific diversity in the degree of elaboration in courtship dance, song and plumage coloration and also for the considerable sex differences in these traits within species. To study the evolution of multimodal sexual signaling in these taxa, we collected data on 85 species and analyzed them in a phylogenetic comparative study. As dances are often displayed in parallel with songs and include behavioral elements to emphasize coloration, they are likely to evolve non-independently of songs and plumage characteristics. Hence, we hypothesized that the degree of elaboration in dance would be associated with song and plumage ornamentation due to correlated responses between traits. Alternatively, each sexual signal may evolve independently of the others under the influence of different aspects of reproductive ecology or life history. Finally, because trait expression occurs in both males and females and can be caused by pleiotropic effects, we predicted correlated exaggerations of the traits between sexes as well. We found that courtship dance, song and plumage coloration evolve independently, as these traits were not correlated among species in either sex (i.e. the presence of female song were not related to female dance repertoire). However, we found evidence for correlated responses between the sexes, as species that have males with complex dances or colorful plumage also have females with exaggerated traits. Yet, selection factors acting on these traits were only partially shared between sexes. While coloration can be predicted by intraspecific brood parasitism and dance by body size in females, we were unable to reveal similar relationships in males. Our results indicate that different secondary sexual characters in Estrildids finches evolved under the influence of complicated selection factors, in which both correlated responses between sexes as well as independent selective mechanisms play roles.